Social Media Networks and Stock Price Synchronicity: Evidence from a Chinese Stock Forum. - Guo, Feng; Lyu, Bin; Lyu, Xiaoliang; Zheng, Jiandong (Abacus, 2025)
The widespread communication and interaction between small investors on social media in the capital market has resulted in the formation of a social media network specific to listed companies. Using a unique dataset from an active online stock forum in China, we construct a social media network of listed companies by assigning listed companies as nodes and common commenters who post in each of the subforums for two listed companies in a year as edges. Then, we investigate the relationship between the network centrality of the listed companies and stock price synchronicity. The results show that there is a significantly negative relationship between the social network centrality of listed companies and stock price synchronicity, indicating that social media networks can improve the price efficiency of capital markets. The mechanism analysis shows that social media networks can produce more corporate‐specific information and improve the efficiency of information dissemination, thus reducing stock price synchronicity.